Lesson Study as a Professional Development Model for Teaching Spatial Ability in Primary STEM - Ergi Bufasi; Ildze Čakāne; Karlis Greitans; Inese Dudareva; Dace Namsone (MDPI AG, 2024)
This study explores the efficacy of a professional development (PD) model that employs lesson study to teach spatial ability skills in primary STEM education. The structure of the PD supported the 'Insights' mechanism by focusing on visualisation, mental rotation, construction and deconstruction, and spatial orientation, which are vital for nurturing students' spatial abilities. The 'Motivation' mechanism was addressed through goal setting in lesson planning, motivating teachers to integrate spatial tasks into their curricula. Continuous feedback and practical support facilitated the 'Technique' mechanism, embedding learned skills into everyday teaching practices. Last, the 'Embed in Practice' mechanisms, including action planning and prompts, were effectively translated into classroom practices, evidencing the model's operational efficacy.